Implementation of The Principles of Islamic Communication in the Digital Era - Tahir, Muhammad; Rayhaniah, Sri Ayu (Borneo International Journal of Islamic Studies, 2022)
Advances in technology can not only provide good benefits but can also have a negative impact, among is the hoax news. The government has been working to overcome this, including socializing digital literacy to the public. This is also in line with Islamic religious teachings that put forward the concept of Islamic communication principles in the interaction of daily life including in communicating digitally so that the motto of Islam that is rahmatan lil' alamin can be achieved. From the concept, researchers are interested in knowing how to implement Islamic communication principles in the digital era. This research is field research with qualitative descriptive approach methods. The object of the research is students who have earned the teaching of Islamic Communication courses. The result of this study is that informants have tried to apply the principles of Islamic Communication, but it has not been able to be applied optimally, due to various obstacles both from internal and external self-informants. Therefore, in addition to knowledge in the form of Islamic communication concepts taught, there also needs to be habituation in the form of in-depth, serious, and continuous training. So that the principles of Islamic Communication are embedded and become self-character.